The Problem of Linguistic Integration: The Social and Linguistic Adaptation of Refugees in the Modern International Space - Vusyk, Hanna; Oliynyk, Elina; Pavlyk, Nelia (Journal of History Culture and Art Research, 2019)
The problem of forced migration is one of the most difficult in today's world space in general and on the European continent in particular, and it requires an integrated approach from the international community to solve this issue. Statistics show that the number of displaced persons in 2018 reached almost 71 million people. Ukraine experiences the problems of migration heavily too. The recent military conflict has forced the inhabitants of Donetsk and Luhansk regions to seek asylum in the other safe parts of the country. Besides, Ukraine's labor migration is rapidly increasing. Millions of Ukrainians live permanently outside of Ukraine. On the other hand, thousands seek asylum from Ukraine. The accumulated international and actual Ukrainian experience suggests that the main problems faced by displaced persons are: a) the question of their legal status in the host territories; b) humanitarian needs (access to education, medical services, social security, etc.), c) official employment, d) psychological and social adaptation, e) negative informational policy, which leads to possible discrimination on national, cultural and other grounds, religion, etc. f) hope only for state financial assistance as the main source of existence, etc. It is especially worth emphasizing that one of the most important aspects of legal and social adaptation of refugees is their interpersonal communication and direct interaction with representatives of state bodies for assistance to refugees, executive authorities, other authorities, public associations, and local people, which is an important element of support and integration of displaced persons. Thus, the priority component of the migration policy of any state is linguistic integration as one of the resources of the socio-cultural adaptation of refugees. Within the framework of the proposed article, we focus on understanding the problems of the language integration of forced displaced persons in the modern international space, promoting the development of speech interaction as the main means of migrants entering the local community, forming socio-communicative competence – a compulsory component of a successful communicative process that also educates the respectful attitude of refugees towards the traditions of the host community.